Behavioural and Cognitive-Behavioural Treatments of Parasomnias - Andrea Galbiati; Fabrizio Rinaldi; Enrico Giora; Luigi Ferini-Strambi; Sara Marelli (Behavioural Neurology)
Parasomnias are unpleasant or undesirable behaviours or experiences that occur predominantly during or within close proximity to sleep. Pharmacological treatments of parasomnias are available, but their efficacy is established only for few disorders. Furthermore, most of these disorders tend spontaneously to remit with development. Nonpharmacological treatments therefore represent valid therapeutic choices. This paper reviews behavioural and cognitive-behavioural managements employed for parasomnias. Referring to the ICSD-3 nosology we consider, respectively, NREM parasomnias, REM parasomnias, and other parasomnias. Although the efficacy of some of these treatments is proved, in other cases their clinical evidence cannot be provided because of the small size of the samples. Due to the rarity of some parasomnias, further multicentric researches are needed in order to offer a more complete account of behavioural and cognitive-behavioural treatments efficacy.